2021
DOI: 10.1111/tpj.15110
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Abscisic Acid Repressor 1 is a susceptibility hub that interacts with multiple Pseudomonas syringae effectors

Abstract: Pathogens secrete effector proteins into host cells to suppress host immunity and promote pathogen virulence, although many features at the molecular interface of host-pathogen interactions remain to be characterized. In a yeast two-hybrid assay, we found that the Pseudomonas syringae effector HopZ1a interacts with the Arabidopsis transcriptional regulator Abscisic Acid Repressor 1 (ABR1). Further analysis revealed that ABR1 interacts with multiple P. syringae effectors, suggesting that it may be targeted as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 100 publications
(107 reference statements)
2
8
0
Order By: Relevance
“…Similar to our observation, induction of Arabidopsis ABR1 gene has been previously shown following infection with PstDC3000 (Schreiber et al, 2021). ABR1 contributes to plant immunity by interacting with Pseudomonas syringae effector molecule HopZ1a along with other different effectors (Schreiber et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to our observation, induction of Arabidopsis ABR1 gene has been previously shown following infection with PstDC3000 (Schreiber et al, 2021). ABR1 contributes to plant immunity by interacting with Pseudomonas syringae effector molecule HopZ1a along with other different effectors (Schreiber et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…is considered a functionally important molecule that interacts with different Pseudomonas syringae effectors (Schreiber et al, 2021). We sought to test our idea that AtERF60 regulates the central key component ABR1 and modulates plant response to biotic stress.…”
Section: Abr1mentioning
confidence: 99%
See 1 more Smart Citation
“…While many AP2/ERFs are positively involved in the ABA signaling and ABA-mediated stress response, a few studies have reported AP2/ERFs function as a negative regulator of ABA response. The Arabidopsis group X ERF ABR1 (AtERF#111) has a dual function as a repressor of ABA response and activator of wounding or host-pathogen interaction [91][92][93]. The Arabidopsis ORA47 (AtERF18) specifically binds to a novel cis element O-box of ABI2 and inhibits ABA and JA signaling [94].…”
Section: Discussionmentioning
confidence: 99%
“…Host defenses may also be enhanced by loss-of-function mutations in T3SE targets that negatively regulate immunity or that are activated by T3SEs to promote pathogen growth. These proteins are referred to as “susceptibility targets” and are of considerable interest as potential mediators of durable pathogen resistance, barring any detrimental effects on plant growth arising from the functional loss of such targets [ 377 , 378 , 379 , 380 , 381 ]. Overall, continued investigations of T3SE functions will address the need to “know thy enemy” and will help drive efforts to breed for durable resistance in agricultural crops.…”
Section: Discussionmentioning
confidence: 99%